2013
DOI: 10.1161/jaha.112.004887
|View full text |Cite
|
Sign up to set email alerts
|

Heart‐Specific Overexpression of Choline Acetyltransferase Gene Protects Murine Heart Against Ischemia Through Hypoxia‐Inducible Factor‐1α–Related Defense Mechanisms

Abstract: BackgroundMurine and human ventricular cardiomyocytes rich in acetylcholine (Ach) receptors are poorly innervated by the vagus, compared with whole ventricular innervation by the adrenergic nerve. However, vagal nerve stimulation produces a favorable outcome even in the murine heart, despite relatively low ventricular cholinergic nerve density. Such a mismatch and missing link suggest the existence of a nonneuronal cholinergic system in ventricular myocardium.Methods and ResultsTo examine the role of the nonne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 34 publications
6
85
0
Order By: Relevance
“…Recently, new reports have focused on the cardiac protective mechanisms of VNS and ACh at the cellular and molecular levels 38, 39 and also from the aspect of cardiac metabolism. 40 Those studies have helped expand our knowledge of the mechanism of cholinergic effects in CHF.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, new reports have focused on the cardiac protective mechanisms of VNS and ACh at the cellular and molecular levels 38, 39 and also from the aspect of cardiac metabolism. 40 Those studies have helped expand our knowledge of the mechanism of cholinergic effects in CHF.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from various transgenic mouse models suggests that this autocrine/paracrine action of ACh is cardioprotective under stressful conditions, such as cardiac hypertrophy and failure, as well as ischemic injury (17,39). However, the molecular mechanisms by which ACh elicits these effects remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the heart acquired ischemic or hypoxic resistance [3]. These results suggested that a non-neuronal cholinergic system could definitely sustain cellular ATP levels and strengthened the link between this system and energy metabolism.…”
Section: Introductionmentioning
confidence: 99%